Bihāra Vidhāna-Sabhā kī Anusūcita Jāti evaṃ Anusūcita Janajāti Kalyāṇa Samiti kā ... prativedana
On the problems of the scheduled tribes of Bihar, India; report of the Samiti of the Legislative Assembly.